The Effect of Experiencing School Violence Victimization and Stress on School Life Adaptation of Adolescents: The Moderated Mediation Model of a Growth Mindset (Medico Legal Update, 2019)
Background/Objectives: The purpose of this study was to investigate the moderating effect of growthmindset on the mediating effect of stress on relationship between school violence victimization and schooladaptation.Method/Statistical Analysis: The subjects of this study were 1,250 students living in H and S city ofChungnam-do, Korea. The collected data are analyzed using correlation analysis, frequency analysis, andmoderating mediation effect.Findings: First, the correlation analysis showed a positive correlation between school violence victimizationand stress, growth mindset and school adaptation. And, the school violence victimization was negativelycorrelated with a growth mindset and school adaptation, and stress was negatively correlated with a growthmindset and school adaptation. Second, the stress mediated the relationship between school violencevictimization experiences and school adaptation. Third, growth mindset moderated the relationship betweenstress and school adaptation. Fourth, growth mindset moderated the mediating relationship of stress betweenschool violence victimization and school adaptation.Improvements/Applications: Finally, based on the results of this study, it was suggested that the program toimprove their growth mindset should be developed to increase school adaptation. In addition, we discussedregional comparisons through nationwide sampling, research on various age groups, and directions forresearch targeting only vulnerable groups.